Addressing service quality issues in higher education: the educational environment evaluation from the students' perspective - Stukalina, Yulia (Technological and Economic Development of Economy, 2012)
Concern about the quality of higher education is on the rise in Europe. To provide quality enhancement of the educational environment higher education institutions should create and implement a strategy for their higher school improvement - a long-term action plan aimed at achieving organisational goals, which includes a) the management of the organisational units as interconnected and interdependent entities; b) the engagement of students in quality assurance activities as enthusiastic and responsible academic community members. This paper discusses the importance of using regular educational environment evaluation, which involves students' indirect participation in decision-making, as one of the most essential quality assurance activities associated with higher school improvement. It also emphasizes the significance of measuring student satisfaction in education, student satisfaction and student motivation being the result of student interactions with the educational environment in the form of students' perceptions of the educational services.